2017
DOI: 10.1002/cctc.201601261
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Phosphine Oxides as Multitalented Preligands En Route to the Chemoselective Palladium‐Catalyzed Oxidation of Alcohols

Abstract: Secondary phosphine oxides O=PHR2 (SPOs) were identified as multitalented preligands for the chemoselective Pd‐catalyzed oxidation of alcohols by a hydrogen‐abstracting methodology. SPOs were found to promote the hydrogen‐abstraction step as well as hydrogen transfer to a Michael acceptor by generating a putative active H−Pd species. The catalytic system operates under neutral conditions and was proven to be compatible with various electrophilic and nucleophilic functionalities within the substrates as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 58 publications
(28 reference statements)
0
11
0
Order By: Relevance
“…Pd complex [[(t-BuPhPO) 2 H] 2 Pd(OAc)] 2 29 was used as oxidative dehydrogenation catalyst for alcohols and a similar outer-sphere mechanism might be operative for this catalyst. [73] Peculiarly, the reduced Pd(0) intermediate can be reoxidized with air without affecting the ligand. In addition, the authors developed a "self-assembling method", which allowed the production of monometallic supramolecular chiral bisphosphinite palladacycles of 29 containing a k 2 -coordinated carboxylate modifiable as desired.…”
Section: Hydrogen Transfermentioning
confidence: 99%
“…Pd complex [[(t-BuPhPO) 2 H] 2 Pd(OAc)] 2 29 was used as oxidative dehydrogenation catalyst for alcohols and a similar outer-sphere mechanism might be operative for this catalyst. [73] Peculiarly, the reduced Pd(0) intermediate can be reoxidized with air without affecting the ligand. In addition, the authors developed a "self-assembling method", which allowed the production of monometallic supramolecular chiral bisphosphinite palladacycles of 29 containing a k 2 -coordinated carboxylate modifiable as desired.…”
Section: Hydrogen Transfermentioning
confidence: 99%
“…We compared the activities of the two palladium‐based catalysts [(PA)‐Pd II ] 1a – b and the platinum‐based catalyst 1c (Scheme ). This selection can be rationalized by the following reasons (i) 1a was previously highlighted as a precursor of hydroxy‐palladium species efficient for the oxidation of alcohols (ii) Compared to 1a or 1b , 1c should exhibit a slightly better oxophilicity, and could therefore be promising. The results are presented in Table .…”
Section: Resultsmentioning
confidence: 99%
“…The use of palladium(II)‐based catalysts in combination with oxygen has driven the design of well‐defined complexes for achieving highly selective oxidation of alcohols Although remarkable achievements have been witnessed, the main issue in these reactions still remains the catalyst degradation. In a recent work, we demonstrated that a way to tackle this problem lies in the use of secondary phosphine oxides (SPOs) as efficient pre‐ligands to stabilise palladium(II) species thus retarding the black palladium deposit (Scheme ) . This particular stability can be attributed to (a) the use of air and water insensitive PA ligands, (b) the hydrogen interaction bonding the two PA ligands leading to a bidentate like that provides a chelate effect, (c) the excellent σ‐electron‐donating properties of this particular type of phosphine that greatly stabilise the Pd II species and finally (d) the formation of a palladium hydride that contains no other X ligand, which thus prevents the reductive elimination and therefore the palladium black formation.…”
Section: Introductionmentioning
confidence: 99%
“…Selective oxidation of alcohols to aldehydes is highly desirable due to their importance as precursors and intermediates in various synthetic protocols, pharmaceutical and agriculture industries ,. Various methods are available for this selective oxidation, however, the development of novel and efficient methodologies is gaining much attention due to the significance of this reaction . Traditional method includes various oxidizing agents (e. g. MnO 2 , CrO 3 , SeO 2 , KMnO 4 , K 2 Cr 2 O 7 , etc.…”
Section: Introductionmentioning
confidence: 99%